Injunctions — Interlocutory and Permanent - Kierans, Patrick E.; Borenstein, Rowena (Intellectual property disputes: resolutions and remedies, 2003)
Intellectual property disputes: resolutions and remedies is designed to fill the void linking the advances in intellectual property law with the law of remedies in Canada by providing a comprehensive and integrated resource for understanding intellectual property law and remedies
OCLC: 1514333875